Relationship between hoof conformation, racing history and fetlock injuries of Thoroughbred racehorses using computed tomography - Jaramillo, Fernando Mosquera (2024)
High-performance athletes walk a fine line that separates maximum performance from injuries. Poor hoof conformation and balance may contribute to injury in equine athletes by affecting distal limb function. Fetlock injuries are common in athletic horses. The fetlock joint is subject to the highest loads of any joint during galloping and is therefore vulnerable to repetitive cyclic fatigue injuries. This study was developed with two main objectives: (1) to investigate the relationship between hoof conformation and racing history in Thoroughbred horses in race training, and (2) to investigate the relationship between hoof conformation and fetlock pathology in Thoroughbred horses in race training using standing computed tomography (CT). Our hypotheses were that measures of poorer foot conformation such as lower dorsal hoof wall angle (DHWA), palmar angle (PA) and hoof pastern angle (HPA) would be associated with longer and more intense racing histories, and that poor hoof conformation, would be associated with more severe bone pathology in the metacarpophalangeal joint. This study included 132 Thoroughbred horses, 33 entire males, 70 geldings and 29 females, with ages ranging from 2 to 8 years. All horses were scanned with a standing equine CT system (Asto Equina®), and all images were reviewed and measurements made using DICOM viewing software (RadiAnt®). The racing history of each horse was accessed via the official website of Racing Australia (https://racingaustralia.horse/). The DHWA was lower in older horses up to 4 years-of- age (coefficient, 95% confidence interval -1.61,-2.85-0.36; P=0.033); and the PA (-0.03,- 0.05 -0.01; P=0.005) and HPA (-0.09,-0.15 -0.04; P<0.001) were lower in horses with greater number of starts. We also found that when comparing international and local horses the DHWA (46.2±2.1º vs. 48.9±2.3º; P<0.001), the PA (0.6±1.5º vs. 1.3±1.8º; P=0.033) and the HPA were lower (162.3± 4.6º vs. 165.5±5.1º; P<0.001) in international horses. Higher grade of palmar/plantar osteochondral disease (POD) was associated with measures of dorsopalmar balance, lower DHWA, and HPA in fore and hind hooves (P<0.024). Higher grade of parasagittal lysis (PSG) was associated with lower DHWA in front and hind hooves (P<0.035). Higher grade of lateral proximal sesamoid bone sclerosis was associated with higher DHWA, PA and HPA in hindlimbs (P<0.021). In conclusion, dorsopalmar hoof conformation is associated with both training/racing history and third metacarpal bone pathology suggesting a common aetiology in Thoroughbred racehorses, however, POD and parasagittal lysis were associated with lower dorsopalmar hoof angles whereas proximal sesamoid sclerosis was associated with higher dorsopalmar hoof angles.